Chaotic Behavior of Soil Radon Gas and Applications - Kamislioglu, Mirac; Kulahci, Fatih (Springer International Publishing Ag, 2016)
The soil Rn-222 concentration non-linear patterns are investigated by the application of various chaos methodologies based on 70 272 measurement data from the East Anatolian Fault Zone, which is one of the world's most active faults. Among these methodologies are Lyapunov exponent, surrogate data, rescaled range (R/S) analysis, Fourier spectrum, phase space reconstruction, mutual information, false nearest neighbors, and correlation dimension. The results indicate that the nonlinear dynamical approach is convenient for characterization and prediction of the Rn-222 concentration dynamics, which are in turn usually used as an earthquake precursor. Behaviour of Rn-222 gas is important in earthquake prediction researches.
Keywords: chaos; radon; earthquake; time-series; nonlinear analysis